2020
DOI: 10.1186/s12870-020-2255-3
|View full text |Cite
|
Sign up to set email alerts
|

Zn/Cd status-dependent accumulation of Zn and Cd in root parts in tobacco is accompanied by specific expression of ZIP genes

Abstract: Background: Root-to-shoot translocation of zinc (Zn) and cadmium (Cd) depends on the concentrations of both metals in the medium. A previous study on tobacco (Nicotiana tabacum) pointed to the contribution of NtZIP1, NtZIP2, NtZIP4 and NtIRT1-like in the regulation of this phenomenon. To learn more, Zn and Cd accumulation, root/ shoot distribution and the expression of ZIP genes were investigated in the apical, middle and basal root parts. Results: We show that Zn/Cd status-dependent root-shoot distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 74 publications
(90 reference statements)
0
43
0
Order By: Relevance
“…Cd enters cells through the ZIP (ZRT, IRT-like protein) transporter, metallothionein, and DMT1 (divalent metal transporter-1). Once in the cell, Cd exhibits cytotoxicity by inhibiting the DNA repair process, cell proliferation and tumor suppressor functions, and causing oxidative stress [ 18 , 19 , 20 , 21 ]. Additionally, Cd inactivates the p53 tumor suppressor protein, which is important for cell cycle arrest and apoptosis regulation, thereby inducing DNA damage and inhibiting DNA repair [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cd enters cells through the ZIP (ZRT, IRT-like protein) transporter, metallothionein, and DMT1 (divalent metal transporter-1). Once in the cell, Cd exhibits cytotoxicity by inhibiting the DNA repair process, cell proliferation and tumor suppressor functions, and causing oxidative stress [ 18 , 19 , 20 , 21 ]. Additionally, Cd inactivates the p53 tumor suppressor protein, which is important for cell cycle arrest and apoptosis regulation, thereby inducing DNA damage and inhibiting DNA repair [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that 50 nM of Ni and 10 nM of Cd alone did not have a significant effect on cell viability; however, when the two heavy metals were used in mixture at these concentrations, cell viability was significantly lower than that of the control group after 48 h. Studies on the synergic [ 23 , 24 ] and antagonistic [ 25 , 26 ] effects of heavy metal co-exposure have been conducted, and their results suggest that the mixed exposure of Ni and Cd has a synergic effect on cell viability. Differences in cell entry and cytotoxic mechanisms of Ni and Cd [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ] have been identified; therefore, their individual properties may be related to these synergic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zn translocation depends on the presence of other metals in the medium, including Cd. Inhibition of translocation has often been described [26][27][28]; however, our recent study showed stimulation in the presence of certain Cd concentrations [28,29]. An increase in Zn translocation was found in the presence of 0.25 and 1 µM Cd in plants grown at low/medium Zn concentrations (0 to 1 µM).…”
Section: Introductionmentioning
confidence: 47%
“…Of the ZIP genes tested in tobacco, only one, NtZIP4A/B, upregulated by Zn deficiency, showed similar transcript levels in all parts of the root at tested combinations of Zn/Cd concentrations [28]. There are two copies of NtZIP4, NtZIP4A, and NtZIP4B (sharing 97.57% homology at the amino acid level) with the same expression pattern in tobacco [31].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation